Persistent Adult Neuroimmune Activation and Loss of Hippocampal Neurogenesis Following Adolescent Ethanol Exposure: Blockade by Exercise and the Anti-inflammatory Drug Indomethacin - Vetreno, Ryan P.; Lawrimore, Colleen J.; Rowsey, Pamela J.; Crews, Fulton T. (Frontiers in Neuroscience, 2018)
Alcohol abuse and binge drinking are common during adolescence, a developmental period characterized by heightened neuroplasticity. Animal studies reveal that adolescent ethanol exposure decreases hippocampal neurogenesis that persists into adulthood, but the mechanism remains to be fully elucidated. Using a rodent model of adolescent intermittent ethanol (AIE; 5.0 g/kg, i.g., 2-days on/2-days off from postnatal day [P]25 to P55), we tested the hypothesis that AIE-induced upregulation of neuroimmune signaling contributes to the loss of hippocampal neurogenesis in adulthood. We found that AIE caused upregulation of multiple proinflammatory Toll-like receptors (TLRs), increased expression of phosphorylated NF-B p65 (pNF-B p65) and the cell death marker cleaved caspase 3, and reduced markers of neurogenesis in the adult (P80) hippocampus, which is consistent with persistently increased neuroimmune signaling reducing neurogenesis. We observed a similar increase of pNF-B p65-immunoreactive cells in the post-mortem human alcoholic hippocampus, an effect that was negatively correlated with age of drinking onset. Voluntary wheel running from P24 – P80 prevented the AIE-induced loss of neurogenesis markers (i.e., nestin and doublecortin) in the adult hippocampus that was paralleled by blockade of increased expression of the cell death marker cleaved caspase 3. Wheel running also prevented the AIE-induced increase of hippocampal pNF-B p65 and induction several neuroimmune NF-B target genes, including TNFα, MCP-1, and IκBα in the adult brain. Administration of the anti-inflammatory drug indomethacin during AIE prevented the loss of neurogenesis markers (i.e., nestin and doublecortin) and the concomitant increase of cleaved caspase 3, an effect that was accompanied by blockade of the increase of pNF-B p65. Similarly, administration of the proinflammatory TLR4 activator lipopolysaccharide resulted in a loss of doublecortin that was paralleled by increased expression of cleaved caspase 3 and pNF-B p65 in the hippocampal dentate gyrus of CON animals that mimicked the AIE-induced loss of neurogenesis. Taken together, these data suggest that exercise and anti-inflammatory drugs protect against adolescent binge ethanol-induced brain neuroimmune signaling and the loss of neurogenesis in the adult hippocampus.